Impact of increased augmentation index and valvuloarterial impedance on symptom recovery after aortic valve replacement for severe aortic stenosis - Jones, Dylan R. (Int J Cardiol Heart Vasc, 2021)
BACKGROUND: Aortic stenosis (AS) is a common valvular disorder with a large symptomatic burden resulting from increased myocardial workload due to valvular obstruction. The contribution of increased afterload from arterial stiffness on symptoms is uncertain. The purpose of this analysis was to determine the symptomatic impact of arterial stiffness as determined by Applanation Tonometry. METHODS: Eighty-eight patients with severe AS undergoing intervention with transcatheter aortic valve replacement (TAVR) (n = 65) or surgical aortic valve replacement (SAVR) (n = 23) were prospectively enrolled. Symptoms were recorded using the NYHA Class, Kansas City Cardiomyopathy Questionnaire (KCCQ) and a 6 min walk test (6MWT) at baseline, and 1- and 6-months post intervention. Pulse Wave Analysis (PWA) using Applanation Tonometry was performed at all reviews, including the augmentation index (AIx). RESULTS: Patients undergoing TAVR were older, with worse renal function and lower aortic valve areas, but were otherwise similar. There was no significant difference between the augmentation index of our AS population compared with an age matched reference population (p = 0.89). Symptoms significantly improved after intervention according to NYHA Class, KCCQ and 6MWT. Additionally, with adjustment, the initial augmentation index correlated with the final KCCQ (Coeff. = −0.383, p = 0.02) and NYHA Class (Coeff. = 0.012, p = 0.03) and a baseline AIx value in the top quartile resulted in a significantly worse final KCCQ (95.1 v 85.2, p = 0.048) relative to the bottom 3 quartiles. CONCLUSIONS: According to our analysis, an elevated baseline AIx is associated with a poorer symptomatic recovery after aortic valve intervention and so is worthy of consideration when assessing potential symptomatic benefit.